The contemporary American juvenile justice system: Revisiting parens patriae: Współczesny amerykański wymiar sprawiedliwości dla nieletnich. Ponowne spojrzenie na parens patriae (Archives of Criminology, 2022)
The American juvenile justice system has undergone significant transformations since itsinception in the late 19th century. In this paper, the authors seek to analyze the historical context of and subsequent reforms to the juvenile system and process in order to determine whether they remain true to their origins of the legal doctrine of parens patriae. Specifically, the authors contrast rehabilitative notions of parens patriae with the “tough on crime” perspective that developed in the 1990s in response to rising crime rates. This debate is illustrated by landmark Supreme Court cases, waivers to the adult system, increases in the use of detention, and the use of “evidence-based programs” to curb further delinquency and prevent violence. The discussion also focuses on the prevalence of systemic racial, ethnic, and gender discrimination, which calls into question the utility of parens patriae and the overall effectiveness of the juvenile justice system.